Estudo da curvatura central das placas cerâmicas para revestimentos : a influência da fusibilidade e coeficiente de expansão térmica da camada de engobe nas curvaturas desenvolvidas durante e após a queima - Rodrigues, Bruno Caio (Universidade Federal de São Carlos, 2017)
Most ceramic tiles have a slip layer and this has a significant influence on the characteristics of the ceramic tiles. In contrast to this reality, the specialized literature on engobes is sparse and superficial. It is known, from experience, that the engobe layer influences the texture of the glazed ceramic tile surface, the curvature of the tiles, the appearance of pathologies such as the water stain, etc. In this context, the objective of the present work was to contribute to a better understanding of the role of the engobe in the ceramic tiles. For this, the influence of the fusibility variation and coefficient of thermal expansion of different engobes on the development of the central curvature of the tiles during and after burning was studied. Four engobes with different coefficients of thermal expansion and different fissures were developed. To determine the fusibility of the engobes, a heating optical microscope was used and a contact dilatometer was used to determine the coefficients of thermal expansion of the engobes and the substrate. In order to evaluate the influence of the differences in the coefficients of thermal expansion and fusibility of the engobes in the development of the central curvature of the tiles the optical fleximeter of heating was used. With the results, it was possible to perceive that the more refractory the engobe in relation to the substrate will be the development of the convex curvature and the more the flux the greater the development of the concave curvature, and the greater the probability of this accompanying the behavior of the substrate until the beginning of the cooling due to the creep mechanism provided by the volume and viscosity of the liquid phases formed during burning. In cooling, the higher the coefficient of thermal expansion of the engobe in relation to the substrate, the greater the development of concave curvature and the smaller the greater the development of the convex curvature.
Study of the centre curvature of ceramic tiles for coatings : the influence of the fusibility and coefficient of thermal expansion of the engobe layer in the curvatures developed during and after the firing
Keywords: Curvatura central; Engobe; Acoplamento; Centre curvature; Engobe; Coupling; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS